Mechanism of Honey Bacteriostatic Action Against MRSA and VRE Involves Hydroxyl Radicals Generated from Honey’s Hydrogen Peroxide - Brudzynski, Katrina; Lannigan, Robert (Frontiers in Microbiology, 2012)
We have recently reported that honey hydrogen peroxide in conjunction with unknown honey components produced cytotoxic effects resulting in bacterial growth inhibition and DNA degradation. The objective of this study was two-fold: (a) to investigate whether the coupling chemistry involving hydrogen peroxide is responsible for a generation of hydroxyl radicals and (b) whether ˙OH generation affects growth of multi-drug resistant clinical isolates. The susceptibility of five different strains of Methicillin-resistant Staphylococcus aureus (MRSA) and four strains of Vancomycin-resistant Enterococcus faecium (VRE) isolates from infected wounds to several honeys was evaluated using broth microdilution assay. Isolates were identified to genus and species and their susceptibility to antibiotics was confirmed using an automated system (Vitek R, Biomérieux R). The presence of the Mec A gene, Nuc gene and Van A and B genes were confirmed by polymerase chain reaction. Results showed that no clinical isolate was resistant to selected active honeys. The median difference in honeys MICs against these strains ranged between 12.5% v/v to 6.25% v/v and was not different from MIC against standard E. coli and B. subtilis. Generation of ˙OH during bacteria incubation with honeys was analyzed using 3’-(p-aminophenyl) fluorescein (APF) as the ˙OH trap. The ˙OH participation in growth inhibition was monitored directly by including APF in broth microdilution assay. The growth of MRSA and VRE was inhibited by ˙OH generation in a dose-dependent manner. Exposure of MRSA and VRE to honeys supplemented with Cu (II) augmented production of ˙OH by thirty-fold and increase honey bacteriostatic potency from MIC90 6.25% v/v to MIC90< 0.78% v/v. Pretreatment of honeys with catalase prior to their supplementation with Cu ions fully restored bacterial growth indicating that hydroxyl radicals were produced from H2O2 via the Fenton-type reaction. In conclusion, we have demonstrated for the first time t